Dopamine D1 receptor agonist A68930 attenuates acute kidney injury by inhibiting NLRP3 inflammasome activation - Jing-Yuan Cao; Le-Ting Zhou; Zuo-Lin Li; Yan Yang; Bi-Cheng Liu; Hong Liu (Elsevier, 2020)
Renal ischemia/reperfusion (I/R) injury is a major cause of acute kidney injury (AKI), characterized by tubulointerstitial inflammation. Currently, progress in developing effective therapies to prevent or ameliorate AKI by anti-inflammation remains slow. Emerging studies have suggested that NLRP3 (the NOD-, LRR- and pyrin domain-containing 3) inflammasome plays a key role in a wide spectrum of kidney disease models including I/R injury. In this study, we investigated the renal protective effects of A68930, a specific agonist for the D-1 dopamine receptor (DRD1), which was recently recognized to downregulate NLRP3 inflammasome via DRD1 signaling. AKI was induced by renal I/R injury and A68930 was intraperitoneally injected 3 times after renal reperfusion. We showed that A68930 significantly ameliorated renal dysfunction. Meanwhile, A68930 markedly reduced macrophages and T cells infiltration, renal pro-inflammatory cytokines production (TNF-α, IL-6, IL-1β), serum pro-inflammatory cytokine (TNF-α and IL-6) and NLRP3 inflammasome activation. Additionally, A68930 attenuated I/R-induced mitochondria injury, which was observed by transmission electron microscopy. In summary, our results demonstrated that activation of DRD1 by A68930 inhibited renal and systematic inflammation, and improved kidney function in I/R induced AKI model, which was probably related to the inhibition of the NLRP3 inflammasome activation.